PENGARUH RASIO GULA AREN DAN KULIT BUAH NANAS TERHADAP KARAKTERISTIK EKO-ENZIM KULIT BUAH NANAS (Ananas comosus) - Yudiantara, Ida Bagus Wiryasuta; Wrasiati, Luh Putu; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2022)
Ecoenzyme is a product of fermentation process that can be used as disinfectant, biocompose, and surface cleaner. In general, ecoenzyme production use organic waste, glucose, and water which fermented for 3 months in anaerob environment before harvested. This research intend to determine the effect of brown sugar addition on characteristics of ecoenzyme from pineapple peels. This research using completely randomized design with single factor. The factor in this research is addition of brown sugar in different ratio. Brown sugar addition of pineapple peels consist of 6 level which are 0:6 ratio; 1:6 ratio; 2:6 ratio; 3:6 ratio; 4:6 ratio; and 5:6 ratio of brown sugar. Variables observed in this research are alcohol contain, pH, and total dissolve solid. The result of this observation indicate that brown sugar addition affected alcohol contain, acidity, and total dissolve solid of ecoenzyme from pineapple peels. Ecoenzyme has higest alcohol contain on day 8 and decresed on day 10. Addition of 5:6 brown sugar ratio was the best treatment with 8,25±0,22% (v/v) alcohol contain, 3,98± 0,11 pH, and 7,87± 1,03 total dissolve solid value.